Effect of ankle range of motion exercise on ankle-brachial index in diabetic foot ulcer patients - Sriwahyuni Sriwahyuni (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Diabetic foot ulcers are a chronic complication of diabetic mellitus that results in skin damage that can extend to tendons, muscles, bones, or joints. Foot ulcers, infections, and peripheral artery disease result in gangrene and lower extremity amputation. Objective: determine the effect of range of motion ankle on ankle brachial index in diabetic foot ulcer patients. Methods: Quantitative research with an approach quasy experimental design with pretest postest design. involving 10 respondents from intervention group I and 10 respondents from intervention group II. Sampling technique with non-probability concecutive sampling. Result: there was a significant difference in the average ankle brachial index of diabetic foot ulcers between the intervention group I and the intervention group II after the ankle range of motion (p= 0.000;). Likewise, it was proven that there was no association between the length of diabetic pain (p=0.752), history of hypertension (p=0.059), smoking habit (p=0.638) and ankle brachial index of diabetic foot ulcers. Conclusion: ankle range of motion exercises, there was a significant increase in the patient's ABI value. This increase in ABI indicates an improvement in blood circulation in the lower extremities, which is very important in the healing process of diabetic foot ulcers. Thus, the ankle range of motion exercise can be considered as one of the effective non-pharmacological interventions in the management of diabetic foot ulcers, helping to improve blood flow and speed up the wound healing process.